2019
DOI: 10.3390/en12244781
|View full text |Cite
|
Sign up to set email alerts
|

Runner Lifting-Up during Load Rejection Transients of a Kaplan Turbine: Flow Mechanism and Solution

Abstract: Dangerous runner lifting-up (RLU) accidents regarding Kaplan turbines, which are widely used in low-head hydropower stations, were frequently reported. Three-dimensional (3D) computational fluid dynamics (CFD) was used to simulate the load rejection transients with guide-vane closing to predict the RLU possibility of the fixed-blade Kaplan turbine in an under-construction hydropower station. It was found that using any linear closing rule, the upward axial water force on the runner was larger than the weight o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…2016; Liu et al. 2019). Their results suggest that a moderate piece-wise guide vane closing process, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…2016; Liu et al. 2019). Their results suggest that a moderate piece-wise guide vane closing process, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that by using any linear closing rule of the guide vane, the upward axial water force on the runner was larger than the weight of rotating parts that started before the guide vanes were closed, putting the hydropower station in a risky situation. It was the suction effect that caused the imbalance, induced by the high rotational speed runner that propels water downstream with a low discharge [31]. Another interesting study was developed by [32], showing a sensitivity analysis of the hydropower system parameters to the rotation speed and discharge.…”
Section: Dynamic Effects In Hydropower Systemsmentioning
confidence: 99%
“…Among them, the Kaplan turbine has been widely used because of its large flow rate, easier maintenance, and high efficiency. [1][2][3] As an important member of hydraulic machinery, it is mainly composed of rotating components (runner) and stationary components (spiral casing, stay vanes, draft tube, etc.). To avoid friction, tip clearance (Figure 1) between the runner blade tip and shroud is existed.…”
Section: Introductionmentioning
confidence: 99%